2020
DOI: 10.1093/jb/mvaa107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ameliorative effects ofTaraxacum syriacumand N-acetylcysteine against acetaminophen-induced oxidative stress in rat liver and kidney

Abstract: Taraxacum syriacum (TS) with natural antioxidant and pharmacological activities may be considered for treatment of oxidative stress induced by acetaminophen (APAP). The aim of the present study was to evaluate the ameliorative effects of the ethanol extract of TS root against hepatorenal toxicity induced by APAP in comparison to N-acetylcysteine (NAC) as a standard drug. Thirty male Wistar rat were randomly divided into five groups. Control group; APAP (1g/kg) group; APAP-NAC (160 mg/kg) group and APAP-TS100 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…These changes in the kidney structure may have been responsible for the lipid peroxidation induced by APAP. These results are consistent with previous studies that described renal histological changes after APAP administration (El-Maddawy and El-Sayed 2018 ; Reshi et al 2020 ; Eshrati et al 2021 ; Wans et al 2021 ; Dallak et al 2022 ; Sohail et al 2022 ). However, treatment with ALC and/or O3FA preserved the normal structure of renal tubules, with only a few mildly dilated glomeruli spaces in some fields.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These changes in the kidney structure may have been responsible for the lipid peroxidation induced by APAP. These results are consistent with previous studies that described renal histological changes after APAP administration (El-Maddawy and El-Sayed 2018 ; Reshi et al 2020 ; Eshrati et al 2021 ; Wans et al 2021 ; Dallak et al 2022 ; Sohail et al 2022 ). However, treatment with ALC and/or O3FA preserved the normal structure of renal tubules, with only a few mildly dilated glomeruli spaces in some fields.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that APAP overdose led to an increase in renal MDA levels and a significant inhibition of major renal antioxidant enzymes (GSH, SOD, and CAT) activities. The decrease in SOD, CAT, and GSH levels, along with an increase in MDA levels, is consistent with previous research on APAP-induced nephrotoxicity (Canayakin et al 2016 ; Abdeen et al 2019 ; Eshrati et al 2021 ; Wans et al 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in the activities of ALT, AST, LDH, ALP and CK enzymes and urea, uric acid and creatinine levels are used as important diagnostic tool for cellular damage and cytotoxicity of toxic agents [21][22][23]. In this study, DZN significantly increased plasma AST, ALT, ALP, CK and LDH activities and urea, uric acid and creatinine levels compared with those of the control group (p<0.05) (Figure 1 and 2).…”
Section: Effects Of Treatments On Plasma Biochemical Parameterssupporting
confidence: 48%
“…MDA is a stable metabolite of the free radical-mediated lipid peroxidation cascade and it is known as a marker of oxidative stress [22,44]. Our results showed a significant increase in the level of MDA in all tissues except spleen (Figure 4), which might have resulted from oxidative damage induced by DZN, might be due to its lipophilicity, whereby it could penetrate easily to the cell membrane and caused membrane lipid peroxidation [9].…”
Section: Effects Of Treatments On Mda Levelmentioning
confidence: 70%